Treating AIDS : Politics of Difference, Paradox of Prevention - THURKA SANGARAMOORTHY (Rutgers University Press, 2014)
The process of completing this book was a long labor of love, hard work, and personal sacrifice. Although at times it was an intensely lonely and isolating practice, it could not have been completed without the love and support of many people. I wish to convey my enormous gratitude to those who have played an important role in the formulation and completion of this journey. Much of this work was inspired by scholars at the Joint Medical Anthropology Program at the University of California, San Francisco and Berkeley, who taught me to think and act in ways that I never dreamed possible. I am particularly thankful to Vincanne Adams, who has always pushed me to think beyond the levels of conventional theoretical paradigms, for providing such valuable advice long after my formal studies ended. I would like to thank Yewoubdar Beyene, Sharon Kaufman, and Edwina Newsom for ensuring that funding was available for this research and for providing much-needed support after the untimely death of Gay Becker. My growth as a scholar and a person would not have been possible without the late Gay Becker. Her intelligence, unwavering support, and positive attitude was always a source of strength for me. Her passion and dedication to her research and lifework closely mirrored her conduct as a mentor. In other words, she was the same person both inside and outside the classroom, in and out of the research context. She was an exceptional person who devoted a great deal of thought and time to others. My gratitude and admiration for her is beyond words.